Experimental burns in an open savanna: Greater fuel loads result in hotter fires - Silva, Marina Oliveira de; Borges, Marcelo Sant'Ana; Fernandes, Luana Gomes [UNESP]; Rodrigues, Naiara Nantes [UNESP]; Watanabe, Yeda Fumie; Joaquim, Daniel Carlino; Oliveira, Clara Slade; Feuchard, Viviane Luzia Silva da; Cyrillo, Joslaine Noely Santos Gonçalves dos; Mercadante, Maria Eugênia Zerlotti; Monteiro, Fabio Morato [UNESP] (Wiley, 2022)
Fire is a main disturbance structuring vegetation worldwide, but few studies have addressed differences in time since last fire and its relationship to fuel load characteristics and fire behavior in Neotropical savannas. We aimed to investigate fire behavior in a Cerrado open savanna of Central Brazil by conducting prescribed fires in areas with different fire-free intervals: one year (FI-1), two years (FI-2), and four years (FI-4). Specifically, we evaluated (1) the amount of live, dead, and total biomass (components of the fuel load); (2) fire behavior, including fire temperatures in three different heights (1 cm belowground, on the soil surface, and 50 cm aboveground), fire duration, residence time, fire intensity, rate of spread, and flame height; and (3) the relationship between soil heating, fuels, and fire by identifying the most important parameters driving soil heating. Total and dead fuel loads were greater in areas with longer fire-free intervals in comparison with areas burned the previous year, with the greatest increment to the fuel bed occurring in the first two years after fire. Greater fuel loads (consequently greater dead fuel loads) resulted in differences in belowground soil heating (-1 cm), where temperatures varied from 39 to 82°C in FI-2 plots and from 40 to 131°C in FI-4 plots; in FI-1 plots temperatures belowground varied from 29 to 68°C. Temperatures on the soil surface and 50 cm aboveground were also greater in plots with longer fire-free intervals, reaching over 400°C on the soil surface and exceeding 500°C 50 cm aboveground. Finally, amount of dead fuel was the best predictor of belowground soil heating, highlighting the importance of fuel loads, which is a key factor to be monitored in fire management plans of Cerrado open savannas.
Keywords: Cerrado; fire behavior fire duration; fire intervals; fire temperatures; Neotropical savanna